2023
DOI: 10.1111/apt.17397
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of including non‐alcoholic fatty liver disease in the definition of metabolic syndrome

Abstract: Summary Background/Aims Metabolic syndrome (MetS) affects over one third of the US adult population. Despite its close association with non‐alcoholic fatty liver disease (NAFLD), the traditional definition of MetS does not account for the presence of NAFLD. The present study thus aims to evaluate the inclusion of NAFLD in the diagnostic criteria of metabolic syndrome on its accuracy of capturing individuals with metabolic dysregulation and its prediction of adverse events. Methods Data collected from NHANES be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Clarissa Elysia Fu et al illustrated that the NAFLD increased the incidence of CVD and mortality (27). Several studies suggested that adding NAFLD into the de nition of MetS could contribute to determine a greater proportion of participants with greater metabolic risk (42,43). A study performed in 533 healthy Japanese women indicated that coexistence of MetS and sarcopenia could increase the risk of CVD as well (44).…”
Section: Discussionmentioning
confidence: 99%
“…Clarissa Elysia Fu et al illustrated that the NAFLD increased the incidence of CVD and mortality (27). Several studies suggested that adding NAFLD into the de nition of MetS could contribute to determine a greater proportion of participants with greater metabolic risk (42,43). A study performed in 533 healthy Japanese women indicated that coexistence of MetS and sarcopenia could increase the risk of CVD as well (44).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue, Fu et al 6 Are these results clinically important? With some limitations, NAFLD may be easily diagnosed considering the wide availability of ultrasonography, low invasiveness and cost, and surrogate biomarkers make the diagnosis even easier.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 97%
“…In this issue, Fu et al 6 reappraise the issue, testing the predictive power for cardiovascular risk of a new definition (MetS2), adding biomarker‐assessed NAFLD to the five clinical features of MetS, in 46,184 individuals in the NHANES population. The original MetS criteria (≥3/5) were identified in 15,027 cases (32.5%); MetS2 criteria (≥3/6 components) were fulfilled in 18,721 (+8%), adding individuals with two original components plus ruled‐in NAFLD.…”
Section: Figurementioning
confidence: 99%
“…
Editors,We read with interest the article by Fu and colleagues titled 'The prognostic value of including non-alcoholic fatty liver disease in the definition of metabolic syndrome'. 1 There is now widespread recognition that fatty liver disease is at its core a disorder of systemic metabolic dysregulation with low-grade meta-inflammation. The phenotypic manifestations in people are modified by various factors including genetics, the environment and dysbiosis.
…”
mentioning
confidence: 99%
“…MAFLD can be positively diagnosed in the presence of steatosis and clearly defined markers of systemic metabolic dysfunction. 2,3 In the study by Fu et al, 1 it is therefore unsurprising that expanding the metabolic syndrome definition to include individuals with liver fat (MetS2) resulted in the identification of more patients with increased all-cause and cardiovascular mortality. The 3694 individuals picked up by the expanded MetS2 criteria have MAFLD by definition (they all had steatosis with at least 2 additional markers of metabolic dysfunction).…”
mentioning
confidence: 99%